Analysis of long-term visual quality with numerical 3D ray tracing after corneal crosslinking treatment - Schedin, Staffan; Hallberg, Per; Behndig, Anders (Applied optics. Optical technology and biomedical optics, 2017)
A numerical 3D ray tracing model was used to evaluate the long-term visual effects of two regimens of corneal crosslinking (CXL) treatment of 48 patients with the corneal degeneration keratoconus. The 3D ray tracing analyses were based on corneal elevation data measured by Scheimpflug photography. Twenty-two patients were treated with standard CXL applied uniformly across the corneal surface, whereas 26 patients underwent a customized, refined treatment only at local zones on the cornea (photorefractive intrastromal CXL; PiXL). Spot diagrams, spot root-mean-square (RMS) values, and Strehl ratios were evaluated for the patients prior to and 1, 3, 6, and 12 months after treatment. It was found that the group of patients treated with PiXL, on average, tended to attain a long-term improvement of the corneal optical performance, whereas only minor changes of the optical parameters were found for group treated with standard CXL. Our results confirmed that standard CXL treatment stabilizes the corneal optical quality over time, and thus halts the progression of the corneal degeneration. In addition to stabilization, the results showed that a significantly higher proportion of subjects treated with PiXL improved in RMS, 3, 6, and 12 months after treatment, compared to with CXL (p<0.05). This finding indicates that the PiXL treatment might improve optical quality over time.